Optimization of Organ Dose and Reduction of Radiation Exposure in Portable X-ray Imaging of Neonates: Utilizing the ALARA-GR Program - Kim, Kwanghyun; Kim, Eunhye; Lim, Cheonghwan; Han, Jaebok (Journal of Neonatal Surgery, 2025)
Portable X-ray imaging is vital for neonates, especially those with very low birth weight (VLBW), in neonatal intensive care units (NICUs), but improper collimation and variations in incubator structures can lead to increased radiation exposure and compromised image quality. This study aimed to evaluate the impact of collimation settings on neonatal organ doses using the ALARA-GR program to optimize radiation exposure and raise awareness among radiologic technologists. Simulations were conducted for neonates undergoing chest and abdominal X-rays with standard dose conditions (60 kVp, 1.25 mAs) and two different field sizes: a properly collimated field (5×7 inches) and a larger, uncollimated field (8×10 inches). Results showed that gender-based differences in organ doses were minimal, but female neonates received significantly higher doses in the uterus, ovaries, and bladder compared to male neonates. Increasing the field size from 5×7 inches to 8×10 inches resulted in substantial increases in organ doses, with doses in critical organs such as the uterus, prostate, testes, and bladder rising by factors of 9, 10, and 12, respectively. The study concluded that expanding the exposure field increased organ doses by 2.4 times for chest X-rays and 1.9 times for abdominal X-rays. Proper collimation significantly reduced radiation exposure, highlighting the importance of standardized collimation training to improve neonatal radiographic safety and minimize unnecessary radiation exposure in NICUs.